Sowing the seed? : human impact and plant subsistence in Dutch wetlands during the late Mesolithic and early and middle Neolithic (5500-3400 cal BC) - Out, Welmoed Aave, 1978- (Archaeological studies Leiden University ;, 2009)
Samenvatting (Dutch summary); Dankwoord; Curriculum vitae